2022
DOI: 10.1186/s13024-022-00544-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of NURR1 in metabolic abnormalities of Parkinson’s disease

Abstract: A constant metabolism and energy supply are crucial to all organs, particularly the brain. Age-dependent neurodegenerative diseases, such as Parkinson’s disease (PD), are associated with alterations in cellular metabolism. These changes have been recognized as a novel hot topic that may provide new insights to help identify risk in the pre-symptomatic phase of the disease, understand disease pathogenesis, track disease progression, and determine critical endpoints. Nuclear receptor-related factor 1 (NURR1), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 246 publications
1
14
0
Order By: Relevance
“…A strong activation of microglia (Mic) is observed in the brain of PD patients, which is not a widespread inflammatory response but has specific pathological outcomes in specific areas, which is closely related to the death of dopaminergic (DA) neurons in the SN . The activation of microglia plays a more important role in the pathogenesis and progression of PD . Interestingly, here, we identified that a natural compound derived from plantain seeds, PMS, could alleviate SN damage in PD mice by reducing microglia polarization .…”
Section: Discussionmentioning
confidence: 84%
“…A strong activation of microglia (Mic) is observed in the brain of PD patients, which is not a widespread inflammatory response but has specific pathological outcomes in specific areas, which is closely related to the death of dopaminergic (DA) neurons in the SN . The activation of microglia plays a more important role in the pathogenesis and progression of PD . Interestingly, here, we identified that a natural compound derived from plantain seeds, PMS, could alleviate SN damage in PD mice by reducing microglia polarization .…”
Section: Discussionmentioning
confidence: 84%
“…Nuclear receptor subfamily 4 group A, or simply NR4A, proteins for instance are nuclear receptor (NR) transcription factors that play a regulatory role in neuronal development, in ammation, and memory formation 28 . The associated disorders are related to dopaminergic dysfunction, including PD, schizophrenia, and manic depression 29,30 . GADD45B, on the other hand, is a neuronal activity sensor induced by neuronal stress and essential for adult neurogenesis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Nurr1, a transcription factor of the NR4A subgroup of nuclear receptor superfamily, plays key roles in the development and maintenance of DA neurons 20 , 22 , 53 . Nurr1 deletion in adult DA neurons gives rise to behavioral impairments, DA deficits including decreased TH, DAT and VMAT2 in the striatum, and loss of DA fibers in the midbrain and striatum 23 , 54 .…”
Section: Discussionmentioning
confidence: 99%